Evaluating cholinesterases inhibition by BAC and DDAC biocides: A combined experimental and theoretical approach - Mouawad, Lynn; Esque, Jeremy; André, Isabelle; Istamboulie, Georges; Catanante, Gaëlle; Noguer, Thierry (Biochimica et biophysica acta. Biomembranes, 2024)
Disinfectant biocides are chemicals that are heavily used for disinfection purposes in households, hospitals, and agrifood industry. The most common type of biocides are quaternary ammonium compounds (QAs), notably benzalkonium chloride (BAC) and didecyldimethylammonium chloride (DDAC), which have been shown to inhibit cholinesterases. This study aims to evaluate the effect of these biocides towards different cholinesterases using both enzyme inhibition and molecular docking experiments. Acetylcholinesterase (AChE) from Drosophila melanogaster (DM-AChE), Electrophorus electricus (EE-AChE), bovine erythrocytes (BE-AChE) and butyrylcholinesterase from horse serum (BChE) were selected for this study. Using a colorimetric assay, all these enzymes were shown to be inhibited in a competitive form by both biocides, BAC and DDAC, with the exception of DM-AChE, which was inhibited in a non-competitive manner by BAC. Molecular docking experiments enabled to identify structural determinants involved in the different modes of inhibition observed. More particularly, our results suggest that non-competitive inhibition of DM-AChE by BAC could be related to the binding of the inhibitor into a more extended active site compared to other cholinesterases. •A rapid colorimetric microplate test was developed to study cholinesterase inhibition by quaternary ammonium biocides.•4 different enzymes were tested including 3 acetylcholinesterases and 1 butyrylcholinesterase.•In silico molecular docking allowed confirmation of the results obtained by enzymatic methods.